The Power of the Agile Business Analyst - JAMIE LYNN COOKE (IT Governance Ltd, 2013)
Agile approaches empower development teams to deliver the greatest business-value software solutions that can be achieved within the time, resourcing, and budget constraints of each project. These approaches focus the Agile team members on building the highest-priority features, on replacing reams of documentation with face-to-face communication, on identifying (and addressing) risks as early as possible in the project timeline, and on continuously reviewing and adapting the developed solution to meet the ongoing needs of the business. One of the core strategies to achieve these objectives is encouraging the Agile development team to work as closely as possible with business users throughout the project timeline. This ongoing interaction enables the Agile developers to better understand the business users' requirements and priorities, reduces their mutual dependence on written specifications, focuses the development team on continually delivering the highest-priority capabilities in the software, and confirms the delivered solution genuinely meets the needs of the business. Although specific Agile methods, such as Scrum, XPÂ®, Lean, and DSDM, differ in their approaches to delivering high business-value solutions, each of these methods equips the Agile developers with practices and tools that are designed to increase the quality, relevance, and extensibility of the software that the team delivers. The Agile community, as a whole, also provides developers with countless supporting resources, including books, websites, forums, and conferences where Agile development issues can be raised, discussed, and jointly addressed by the group. The interesting thing is that, where Agile approaches go to great lengths to provide the developers with the foundation they need to deliver high-value software solutions, there is relatively little equivalent support provided for the business users. In most Agile methods, the business user is solely responsible for the identification, requirements gathering, clarification, and assignment of priorities for the requested system capabilities. These methods generally work from the assumption that the business users have separately collaborated with all the relevant stakeholders prior to each joint planning session, and that their collective input is accurately represented. Agile methods also assume the business users have sufficient knowledge, vision, and objectivity to ensure the capabilities they are requesting represent the best possible solution for the organization. Likewise, Agile methods anticipate that the business users will be available throughout the project to provide the Agile developers with accurate and timely ongoing feedback. Although the intention of having Agile development teams working directly with business areas throughout the project is a noble one, without a reasonable level of support for the business users, the execution can fall short.